2008
DOI: 10.1074/jbc.m802846200
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of Murine Caspase-9 by the Protein Kinase Casein Kinase 2 Regulates Its Cleavage by Caspase-8

Abstract: Previous studies from our laboratory had indicated that cytochrome c-independent processing and activation of caspase-9 by caspase-8 contributed to early amplification of the caspase cascade in tumor necrosis factor (TNF)-␣-treated murine cells. Here we show that murine caspase-9 is phosphorylated by casein kinase 2 (CK2) on a serine near the site of caspase-8 cleavage. CK2 has been shown to regulate cleavage of the pro-apoptotic Bid protein by phosphorylating serine residues near its caspase-8 cleavage site. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
1
2

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 48 publications
1
32
1
2
Order By: Relevance
“…Likewise, cytochrome c was not released from mitochondria ( Figure 1D), contrary to SUDHL4 cells. Therefore, since caspase-9 has been demonstrated to be a direct target of caspase-8, 18 these data suggest that activation of caspase-9 and caspase-2 in VAL and RL cells may directly result from caspase-8 activation, but not from mitochondria. In line with this hypothesis, TRAIL stimulation in these resistant cells induced no loss of mitochondrial potential (MMP) ( Figure 1E) and caspase-9 cleavage was inhibited by caspase-8 inhibitors (data not shown).…”
Section: Val and Rl B-cell Lines Display Strong Resistance To Trail-imentioning
confidence: 99%
“…Likewise, cytochrome c was not released from mitochondria ( Figure 1D), contrary to SUDHL4 cells. Therefore, since caspase-9 has been demonstrated to be a direct target of caspase-8, 18 these data suggest that activation of caspase-9 and caspase-2 in VAL and RL cells may directly result from caspase-8 activation, but not from mitochondria. In line with this hypothesis, TRAIL stimulation in these resistant cells induced no loss of mitochondrial potential (MMP) ( Figure 1E) and caspase-9 cleavage was inhibited by caspase-8 inhibitors (data not shown).…”
Section: Val and Rl B-cell Lines Display Strong Resistance To Trail-imentioning
confidence: 99%
“…Recent studies have also shown the positive feedback loop of the activation of caspase-3, -8 and -9 in some apoptotic models. Gil [12] and McDonnell [13,14] found that active Fenglian Xiao and Weijie Gao contribute equally to this paper.…”
Section: Introductionmentioning
confidence: 95%
“…In addition to regulating caspase activity by phosphorylating substrates, CK2 can also directly regulate the activity of the caspases themselves. In mice, caspase 9 is protected from caspase 8 cleavage by CK2 phosphorylation, and loss of the phosphorylation site leads to induction of apoptosis [99]. By phosphorylating caspase 2, CK2 inhibits caspase 2 dimerization, therefore preventing its activation [100].…”
Section: Ck2 In the Induction Of Apoptosismentioning
confidence: 99%